Sintren dan Perkembangannya: Studi Kasus Tari Sintren Santri Sanggar Windu Ajibudaya Kaso Tengah Kecamatan Doro Kabupaten Pekalongan Jawa Tengah - Laura Andri R.M (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Traditional arts or folk art have certain characteristics that lead to the peculiarities of each region. This art emerged as a result of human cultivation to express the value of beauty, pleasure, hope for both himself and others. The existence of socio-cultural-religious experiences in the community gave birth to traditional arts which contained many values of wisdom. Sintren dance that developed in Doro Pekalongan Subdistrict is one of the traditional arts as a result of the aesthetic product of its people. Like other traditional arts, the shift in function and form is also experienced by this Sintren art. By using the Windu Ajibudaya Kaso Tengah Studio as an object of research as well as the use of a qualitative descriptive approach and observation, interview, documentation techniques, it can be seen how the art group's efforts in preserving its artistry. As well as what teachings and symbolic meanings are contained in them.